2022
DOI: 10.1186/s13756-022-01073-3
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and validation of a nomogram to predict the in-hospital death risk of nosocomial infections in cancer patients

Abstract: Background Attributed to the immunosuppression caused by malignancy itself and its treatments, cancer patients are vulnerable to developing nosocomial infections. This study aimed to develop a nomogram to predict the in-hospital death risk of these patients. Methods This retrospective study was conducted at a medical center in Northwestern China. The univariate and multivariate logistic regression analyses were adopted to identify predictive factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 40 publications
1
13
1
Order By: Relevance
“…The percentage of malnourished patients in our study concurs with previously reported data in cancer hospitalized patients and according to GLIM criteria [ 29 ]. Compared to other studies reporting NI in cancer patients, the frequency of NI in our study was higher [ 20 ]. These differences may be partly attributed to the demographic and clinical characteristics of the study population.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…The percentage of malnourished patients in our study concurs with previously reported data in cancer hospitalized patients and according to GLIM criteria [ 29 ]. Compared to other studies reporting NI in cancer patients, the frequency of NI in our study was higher [ 20 ]. These differences may be partly attributed to the demographic and clinical characteristics of the study population.…”
Section: Discussioncontrasting
confidence: 98%
“…Nosocomial infections (NI) are one of the many consequences of malnutrition in a hospital setting, affecting care and outcomes in cancer and increasing healthcare costs [19]. Cancer patients are more vulnerable to developing severe infections (especially NI) owing to the malignancy itself and its treatments [20,21]. Earlier studies have shown that 2.1% to 48% of cancer patients develop NI, varying widely across regions [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Our results cannot be generalized to other centers because we did not have external validation. Third, similar to other models for predicting nosocomial infection, 27,44,46 our model predicts the probability of nosocomial infection, but does not describe the exact infection site.…”
Section: Model Clinical Applicationmentioning
confidence: 88%
“…Meanwhile, hypoproteinemia was a statistically screened independent risk factor associated with carbapenem resistance in our study, and yet has rarely been observed to be related to carbapenem resistance in previous studies. Given that hypoproteinemia has been linked to disease progression and clinical prognosis in different clinical settings ( Murthy et al., 2018 ; Aziz et al., 2020 ; Omiya et al., 2021 ; Jiang et al., 2022 ), it was also incorporated into the plotting of the carbapenem resistance nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, nomograms have been diffusely applied in medical research as an effective complementary tool to implement clinical decisions for clinicians ( Balachandran et al., 2015 ; Wu et al., 2020 ; Lin et al., 2020 ; Song et al., 2021 ; Dong et al., 2021 ; He et al., 2022 ). As a graphical tool, compared with traditional predictive scoring systems based on regression analysis, the nomogram can provide a visual representation of the complex statistical model and accurately estimate the individual probability of a clinical event by integrating multiple predictive variables that can diagnose diseases or predict clinical outcomes ( Park, 2018 ; Jiang et al., 2022 ). However, nomograms predicting the risk factors of mortality and carbapenem resistance in HM patients with GNB BSI have rarely received attention.…”
Section: Introductionmentioning
confidence: 99%